Understanding the boosted sodium storage behavior of a nanoporous bismuth-nickel anode using operando X-ray diffraction and density functional theory calculations. Issue 22 (22nd May 2019) - Gao, Hui; Song, Lin; Niu, Jiazheng; Zhang, Chi; Kou, Tianyi; Sun, Yue; Qin, Jingyu; Peng, Zhangquan; Zhang, Zhonghua
Abstract : A novel channel-enhanced strategy upon atomic substitution via a dealloying process for the improved Na storage of alloying-type anodes for SIBs. Abstract : To improve the electrochemical performance of metal-based anodes for sodium ion batteries (SIBs), predominant efforts are focused on a nanoporous architecture, metallic alloys, and composites with a conductive substrate. Herein, we for the first time propose a novel channel-enhanced strategy to promote the Na storage performance of alloying-type anodes. We further fabricated a nanoporous (np) Bi50 Ni50 alloy which has intra-lattice straight ion channels, via a facile dealloying of ternary Mg–Bi–Ni precursors with suitable Bi/Ni atomic ratios. As an anode for SIBs, the np-Bi50 Ni50 alloy exhibits a superior electrochemical performance (specific capacity, rate capability, and cycling stability) as compared to np-Bi75 Ni25 without such ion diffusion channels. Electrochemical measurements and density functional theory calculations confirm that the significant performance improvement of np-Bi50 Ni50 stems from the intra-lattice straight ion channels, which not only shorten the diffusion distance and lower the inhibition from surrounding atoms during the Na + diffusion, but also efficiently migrate the lattice deformation and thus improve the stability of the electrode. More importantly, operando X-ray diffraction results reveal that both the np-Bi50 Ni50 and np-Bi75 Ni25 anodes share a similar Na storage mechanism.